Bilingual phonology in dichotic perception: A case study of Malayalam and English voicing. Issue 1 (22nd July 2020) - Mandal, Sayantan; Best, Catherine T.; Shaw, Jason; Cutler, Anne
Abstract : Listeners often experience cocktail-party situations, encountering multiple ongoing conversations while tracking just one. Capturing the words spoken under such conditions requires selective attention and processing, which involves using phonetic details to discern phonological structure. How do bilinguals accomplish this in L1-L2 competition? We addressed that question using a dichotic listening task with fluent Malayalam-English bilinguals, in which they were presented with synchronized nonce words, one in each language in separate ears, with competing onsets of a labial stop (Malayalam) and a labial fricative (English), both voiced or both voiceless. They were required to attend to the Malayalam or the English item, in separate blocks, and report the initial consonant they heard. We found that perceptual intrusions from the unattended to the attended language were influenced by voicing, with more intrusions on voiced than voiceless trials. This result supports our proposal for the feature specification of consonants in Malayalam-English bilinguals, which makes use of privative features, underspecification and the "standard approach" to laryngeal features, as against "laryngeal realism". Given this representational account, we observe that intrusions result from phonetic properties in the unattended signal being assimilated to the closest matching phonological category in the attended language, and are more likely for segments with a greater number of phonological feature specifications.